Bacteriological Contamination of Drinking Water Supply from Protected Water Sources to Point of Use and Water Handling Practices among Beneficiary Households of Boloso Sore Woreda, Wolaita Zone, Ethiopia. (13th April 2020) - Gizachew, Matusala; Admasie, Amha; Wegi, Chala; Assefa, Etagegnehu
Abstract : The quality of drinking water is a powerful environmental determinant of health. Water becomes contaminated with faecal material due to inadequate protection of the source, unhygienic practices of the community at the source, and poor household handling practices. The objective of this study was to assess the level of bacteriological contamination of drinking water supply from protected water sources to point of use and water handling practices among beneficiary households of Boloso Sore woreda, Wolaita zone, Ethiopia. A cross-sectional survey and bacteriological analysis of water were conducted in January 2019. The study included 545 households for water handling practices, and 75 samples from stored water from households and eighteen water sources were included for faecal coliform test. Data were analyzed using SPSS v21.0. Descriptive and logistic regression statistical models were used. Sixty percent of shallow wells, 60% of protected hand-dug wells, and 25% of protected on-spot springs were found positive for faecal coliform. In general, 44% of water source samples and 91% of household water samples were positive for faecal coliform. In general, 38% of households were practicing unsafe water handling practices. High school and above level of education (AOR = 3.37, 95% CI: 1.03, 11.57), getting higher monthly income (AOR = 2.37, 95%CI: 1.96, 5.85), households with small family size (AOR = 1.81, 95% CI: 1.15, 2.83), frequency of water collection twice a day (AOR = 2.88, 95% CI:1.56, 5.33), and presence of water payments (AOR = 0.42, 95% CI: 0.24, 0.72) were significantly associated with water handling practice. Unsafe water handling was a common practice in the study area, and water sources and household water storage were not free of faecal coliform, indicating noncompliance with the World Health Organization water quality guideline. Hence, capacity building is mandatory for the protection and management of water sources and safe water handling practices in the household and community.